Growth and mineral composition of Bell Bauhinia seedlings (Bauhinia forficata Link) as affected by N, P, and K (Revista Brasileira de Plantas Medicinais, 2000)
The effects of soil fertilization with N, P and K were evaluated on the growth of Bauhinia forficata Link seedlings over 110 days. Twenty-four treatments were made for this experiment consisting of 3 doses of nitrogen: 0, 75, and 150 mg.dm-3, 4 doses of phosphorus: 0, 100, 200, 400 mg.dm-3 two doses of potassium: 0 and 100 mg.dm-3 , on a 3 x 4 x 2 completely randomized factorial scheme, with five replications. Seedling growth was evaluated using: height, stem diameter, and by the dry matter weight of the aerial part, leaf blade, roots, and total dry matter root/aerial ratio of plants collected 30 and 105 days after sowing. Stem diameter was 4.0mm when 148.26 mg.dm-3  of phosphorus was applied resulting in 90% of the maximum yield. There was a positive and quadratic response for leaf blade dry matter from P and N, when 90% of the maximum yield (7.91 g of DM) was obtained by applying 189.59 mg.dm-3  of phosphorus and 75 mg.dm-3  of nitrogen. B. forficata was responsive to mineral fertilization in relation to growth at the cutting phase. The application of phosphorus and nitrogen in the doses presented in this study, favoured the early growth of the plant and potassium did not show a significant response.